Strategies for the sampling of hydrogen at refuelling stations for purity assessment. (11th October 2021) - Arrhenius, Karine; Aarhaug, Thor; Bacquart, Thomas; Morris, Abigail; Bartlett, Sam; Wagner, Lisa; Blondeel, Claire; Gozlan, Bruno; Lescornez, Yann; Chramosta, Nathalie; Spitta, Christian; Basset, Etienne; et al.
Abstract: Hydrogen delivered at hydrogen refuelling station must be compliant with requirements stated in different standards which require specialized sampling device and personnel to operate it. Currently, different strategies are implemented in different parts of the world and these strategies have already been used to perform 100s of hydrogen fuel sampling in USA, EU and Japan. However, these strategies have never been compared on a large systematic study. The purpose of this paper is to describe and compare the different strategies for sampling hydrogen at the nozzle and summarize the key aspects of all the existing hydrogen fuel sampling including discussion on material compatibility with the impurities that must be assessed. This review highlights the fact it is currently difficult to evaluate the impact or the difference these strategies would have on the hydrogen fuel quality assessment. Therefore, comparative sampling studies are required to evaluate the equivalence between the different sampling strategies. This is the first step to support the standardization of hydrogen fuel sampling and to identify future research and development area for hydrogen fuel sampling. Highlights: Detailed description of different strategies for sampling hydrogen at the nozzle. Discussion on the representativeness of the sample collected. Results from different stability studies for gaseous species in different cylinders. Highlight the need of comparative studies to assess equivalence between strategies.